2010
DOI: 10.1063/1.3268626
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bonded network properties in liquid formamide

Abstract: Molecular dynamics simulations have been performed for liquid formamide using two different types of potential model (OPLS, Cordeiro). The structural results obtained from simulation were compared to experimental (x-ray and neutron diffraction measurements) outcomes. A generally good agreement for both models examined has been found, but in the hydrogen bonded region (2.9 A) the Cordeiro model shows a slightly better fit. Besides the evaluation of partial radial distribution functions, orientational correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 46 publications
0
40
0
Order By: Relevance
“…On the other hand, we can characterise these systems as a complex networks, which, in turn, may be described by their topological properties. Recently, some of the present authors have described the topology of hydrogen bonded aggregations in water and pure liquid formamide [37][38][39] . It could be demonstrated that although both alcohol and water molecules form hydrogen bonds readily, significant differences are present in terms of the H-bonded environment of the two species in water-methanol and water-ethanol mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we can characterise these systems as a complex networks, which, in turn, may be described by their topological properties. Recently, some of the present authors have described the topology of hydrogen bonded aggregations in water and pure liquid formamide [37][38][39] . It could be demonstrated that although both alcohol and water molecules form hydrogen bonds readily, significant differences are present in terms of the H-bonded environment of the two species in water-methanol and water-ethanol mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…From Bakó et al, the mean number of hydrogen bonds per FA molecule is 3.21, while the number for water is 3.35. 27 Cordeiro et al reported the formation of three hydrogen bonds between a FA molecule and its neighbouring waters, while two and one hydrogen bonds are formed in the case of methylformamide and DMF-water mixtures, respectively. As part of their conclusion, they observed that the strength of the amide-water hydrogen bond increases with decreasing the number of hydrogen bonds per amide.…”
Section: W Th = -Ar/6dmentioning
confidence: 99%
“…Cordeiro [13] in 1997 performed MC simulations to derive a force field of formamide able to reproduce the experimental liquid density and heat of vaporization. Bako et al published later on [14] an analysis of the hydrogen bond structure of formamide using the OPLS [5] and Cordeiro's [13] potentials. It has been suggested that the failure of current force fields to reproduce the dielectric constant of liquids is connected to the atomic charges that have been derived without considering intermolecular polarization effects, which would be relevant in condensed phases.…”
Section: Introductionmentioning
confidence: 99%